Investigation of a theoretical model for the rotational shot put technique - Kato, T.; Maeda, K.; Mizushima, J.; Maeda, A. (ISBS Proceedings Archive (Michigan), 2022)
This study aimed to investigate the causal relationships among biomechanical variables for achieving high release velocity in male shot putter and create a theoretical model for the rotational shot put technique. The throwing motions of 22 male shot putters were videotaped and analysed using the 3D DLT method. Path analysis was used to examine causal relationships among biomechanical variables. The examined model consisted of three kinetic and eight kinematic variables that significantly related to a higher release velocity directly or indirectly. Two key factors were identified in shot put performance with the rotational technique: (1) increasing of impulse of the shot at delivery phase, and (2) creating greater linear and angular momentum before delivery. Future research should confirm or extend this potential causal mechanism of contributors to shot release velocity.